Types Of Rice Pests (Oryza sativa L) In Rice Fields In Tebat Karai District, Kepahiang Regency - Agustina, Ria Yopika; Meti Herlina; Pariyanto (Utami Publisher, 2025)
This study aims to determine the types of pests in rice plants in Tebat Karai District, Kepahiang Regency. This research method uses a direct survey method to the field and uses an exploration method in sampling. quasi-experiment, with a quantitative approach and using a pretest-posttest non-equivalent control group design. The results of the study showed that there were 10 families and 11 species, namely the Estrildidae family 1 species (Lonchura maja) as many as 32 individuals, the Prygomorphidae family 1 species (Atractomorpha arenulata) as many as 20 individuals, the Gryllidae family 1 species (Grillis bimaculatus) as many as 5 individuals, the Coreidae family 1 species (Anoplocnemis phasiana) as many as 5 individuals, the Acrididae family 2 species (Locusta migratoria, Oxya chinensis) as many as 15 individuals, the Pentatimidae family 1 species (Podium nigrispinus) as many as 7 individuals, the Allydidae family 1 species (Loptocorisa acuta) as many as 7 individuals, and the Ampullariidae family 1 species (Pila ampullacea) as many as 45 individuals. Oxya chinensis (Green grasshopper) as many as 33 individuals. Ecological factors in rice fields in Tebat Karai District, Kepahiang Regency with air temperatures ranging from 25 °C to 27 °C, humidity ranging from 70% to 85%, and soil pH ranging from 5.0 to 6.1.